Emotional divorce among married employees - Remonda Eshaya Armia; Kajeen Omer (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Emotional divorce is a type of negative communication and the emotional and psychological isolation between marriage people. As a result, their life become as a source of psychological problems. However, they prefer to live alone under one roof, and each of them has its own world far from each other, preferring. The unreal life form without access to an official divorce because of the fear of the the children’s future or the criticism of the society.While the married life continues between them painfully. The objectives of the current research are to identify the level of emotional divorce among married employees in Zakho district in general, and the significance of the differences in that according to the variables: gender, number of years of marriage, educational achievement, and economic status. To achieve the objectives of the research, a measure of emotional divorce was prepared, to fit the requirements of the recent research and the nature of the sample. It consist of (42) items, and the psychometric properties of it have been extracted. Then it was applied to the sample that consisted of (700) couples of employees who were selected among the married couples, then distributed over nine departments in Zakho district in Dohuk governorate. After analyzing the data by using appropriate statistical; the results showed that the level of emotional divorce in general is low, and there are no significant differences in the level of emotional divorce due to the variables of gender, years of marriage, economic status or educational achievement. Depending on the results, a set of recommendations and suggestions were developed.